Diagnosis dan Tata Laksana Dissociated Vertical Deviation - Saphira Evani; Ni Made Ayu Surasmiati; I Wayan Eka Sutyawan (PT Kalbe Farma Tbk., 2024)
Dissociated vertical deviation (DVD) is characterized by an upward deviation of one eye in the absence of any compensatory movement in the other eye. This condition is often seen in strabismus and can cause visual disturbances such as double vision and amblyopia. Its underlying causes are believed to be related to abnormalities of the visual pathways to control eye movements. Treatment options include observation, conservative management, and surgical intervention, depending on the severity and underlying cause.